Budaya Organisasi Lembaga Pendidikan Islam dalam Epistemologi Kuntowijoyo - Hestiana, Ratna; Labaso, Syahrial (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
The formation of organizational culture in Islamic educational institutions is an important element that affects the performance and success of the institution. This study aims to analyse the process of forming organizational culture in Islamic educational institutions through the perspective of the epistemological structure of Kuntowijoyo culture. The method used in this study is a literature study, by examining various relevant literature related to organizational culture, Islamic education, and Kuntowijoyo's thought. The epistemological structure of the Kuntowijoyo culture includes three main components: objectification, subjectification, and intersubjectivities. The results of the study show that Islamic values are objectified in the vision, mission, and policies of Islamic educational institutions; subjectifies through the internalization of these values by individuals in daily practice; and intersubjective through social interaction within the institution. The consistent application of Islamic values in all aspects of the organization has proven to be important in shaping and maintaining a strong organizational culture that is aligned with Islamic principles, which ultimately improves the quality of education and the formation of students' character.